MULA KERJA ROKURONIUM - Tompodung, Sadrakh; Tambajong, Harold F.; Lalenoh, Diana (JURNAL BIOMEDIK : JBM, 2013)
Abstract: Endotracheal intubation needs a muscle relaxant to permit the pipe to get easily into the trachea. Injury of the respiratory tract during this procedure can be avoided by being cognizant of the onsets of action of certain muscle relaxants. Rocuronium is a non-depolarization muscle relaxant with intermediate duration of action and fewer side effects. This study aimed to find out the onset of action of rocuronium. This was an observational study conducted in the operation rooms of Prof. Dr. R.D. Kandou Hospital from November 2012 to January 2013. Samples were patients with ASA 1-2, aged 18 40 years who had been selected by using simple random sampling methods. Midazolam 0,7 mg/kg BW and fentanyl 2 µg/kg BW were used as premedication agents; propofol 2 mg/kg BW as an anaesthetic induction agent; and rocuronium 0,6 mg/kg BW as the muscle relaxant. The rocuronium?s onset of action was measured by using TOF-Watch after the injection of rocuronium until the percentage of muscle relaxation was 0. The results showed that the onset of action in 17 samples (14 females and 3 males) was 151 seconds. The onset of action in females was 65 seconds shorter than in males. A correlation test (P = 0.857) and the chi-square test (P = 0.434) showed no significant correlation between age and the onset of action. There was a significant difference (P < 0.05) between the onset of action and sex showed by the t-test (P = 0.023) and the chi-square test (P = 0.035). Conclusion: The average onset of action of rocuronium was 2 minutes and 31 seconds, with  females having a shorter onset of action of rocuronium. Keywords: onset of action, rocuronium.     Abstrak: Pemasangan pipa trakea memerlukan obat pelumpuh otot untuk memudahkan pipa ini masuk ke saluran napas. Cedera saluran napas akibat pemasangan pipa trakea dapat dihindari dengan mengetahui mula kerja (onset of action) dari obat pelumpuh otot. Rokuronium merupakan obat pelumpuh otot jenis non-depolarisasi dengan lama kerja sedang tanpa efek samping bagi tubuh. Penelitian ini bertujuan untuk mengetahui mula kerja rokuronium dan dilakukan di ruang operasi Rumah Sakit Prof Dr. R.D. Kandou Manado sejak bulan Nopember 2012 hingga Januari 2013. Sampel ialah pasien dengan ASA 1-2, berusia 18-40 tahun, yang dipilih secara simple random sampling. Pasien dipremedikasi dengan midazolam 0,7 mg/kg BB dan fentanil 2 µg/kg BB, diinduksi dengan propofol 2 mg/kg BB dan kemudian diberikan rokuronium 0,6 mg/kg BB secara intra vena. Mula kerja rokuronium diukur antara selesai penyuntikan hingga persentase kelumpuhan otot pada TOF-watch mencapai 0. Hasil penelitian memperlihatkan pada 17 sampel (14 orang perempuan dan 3 orang laki-laki), rerata mula kerja rokuronium 151 detik. Mula kerja rokuronium pada perempuan 65 detik lebih singkat daripada laki-laki. Hasil uji korelasi (P = 0,857) dan uji chi-square (P = 0,434) memperlihatkan tidak terdapat korelasi bermakna antara usia dan mula kerja rokuronium. Terdapat perbedaan bermakna (P < 0,05) antara mula kerja rokuronium dan jenis kelamin yang ditunjukkan dengan uji t (P = 0,023) dan uji chi-square (P = 0,035). Simpulan: Rerata mula kerja rokuronium dengan dosis 0,6 mg/kg BB untuk kedua jenis kelamin 2 menit 31 detik. Perempuan mempunyai mula kerja rokuronium lebih singkat daripada laki-laki. Kata kunci: mula kerja, rokuronium.